2019
DOI: 10.1038/s41598-019-42878-4
|View full text |Cite
|
Sign up to set email alerts
|

SMAD3 directly regulates cell cycle genes to maintain arrest in granulosa cells of mouse primordial follicles

Abstract: Primordial follicles, consisting of granulosa cell (GC)-enveloped oocytes are maintained in a state of developmental arrest until activated to grow. The mechanism that operates to maintain this arrested state in GCs is currently unknown. Here, we show the TGFβ-activated transcription factor SMAD3 is expressed in primordial GC nuclei alongside the cell cycle proteins, cyclin D2 (CCND2) and P27. Using neonatal C57/Bl6 mouse ovaries densely populated with primordial follicles, CCND2 protein co-localised and was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 57 publications
(68 reference statements)
1
30
0
1
Order By: Relevance
“…All of these transcripts have been reported as markers of quiescence 34 38 . Moreover, the key inhibitors of follicular emergence from a quiescent state Smad 2 and Smad3 39 , 40 were upregulated in NR5A2 cKO ovaries (Fig. 5 f).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…All of these transcripts have been reported as markers of quiescence 34 38 . Moreover, the key inhibitors of follicular emergence from a quiescent state Smad 2 and Smad3 39 , 40 were upregulated in NR5A2 cKO ovaries (Fig. 5 f).…”
Section: Resultsmentioning
confidence: 88%
“…Their expression is associated with follicular quiescence while their loss was associated with activation 40 . SMAD3 directly maintains quiescence of granulosa cells by suppressing expression of the proto-oncogene MYC 39 , 61 . Both Smad2 and Smad3 were greater in cKO than CON ovaries, while Myc declined.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the inhibition of type I TGFβ receptors induces an acceleration of oocyte growth and GC proliferation in cultured neonatal mouse ovaries (36). Recently, Hardy and colleagues demonstrated that nuclear SMAD2/3 expression is inversely correlated to cell proliferation in mouse ovary GCs (37), and that the loss of nuclear SMAD3, which controls the expression of cell cycle regulators such as Ccnd2 and Myc, coincides with elevated mTOR signaling to drive cell proliferation in the GCs of growing follicles (38). Comparison of differentially expressed genes between the primordial and primary stage in human GCs has identified JAK/STAT signaling as another actor mediating the primordial-to-primary follicle transition (25,39).…”
Section: Specific Tsc1 Deletion In Mouse Gcs Results In Mtorc1 Signalmentioning
confidence: 99%
“…Chronic alcohol exposure also induced the down‐regulation of Smad3 in the hippocampus in this study. Smad3, one of the Smad proteins that transduce the signals of the TGF‐β family, participates in cell cycle arrest and cell proliferation depending on cell type and circumstances . Smad3 directly induces the expression of Ccnd2 and in turn induces arrested cell cycle in granulosa cells of mouse primordial follicles, while Smad3 directly promotes Nanog, an important stem cell transcription factor, inducing self‐renewal in embryonic stem cells .…”
Section: Discussionmentioning
confidence: 99%
“…Smad3, one of the Smad proteins that transduce the signals of the TGF‐β family, participates in cell cycle arrest and cell proliferation depending on cell type and circumstances . Smad3 directly induces the expression of Ccnd2 and in turn induces arrested cell cycle in granulosa cells of mouse primordial follicles, while Smad3 directly promotes Nanog, an important stem cell transcription factor, inducing self‐renewal in embryonic stem cells . In the study by Epperly et al, Smad3 −/− mice exhibited a high population of bone marrow stromal cells at G2/M phase, implying that knockout of Smad3 − / − leads to alteration of the normal cell cycle.…”
Section: Discussionmentioning
confidence: 99%